Resolution of individual lipids in mixed phospholipid membranes and specific lipid-cytochrome c interactions by magic-angle spinning solid-state phosphorus-31 NMR. - Pinheiro, T; Watts, A (1994)
A model of the inner mitochondrial membrane was constructed with dioleoyphosphatidylcholine (PC), dioleoylphosphatidylethanolamine (PE), and cardiolipin (CL) at a PC:PE:CL molar ratio of 2:2:1, and the interaction of the peripheral membrane protein cytochrome c with this mixed membrane has been investigated by static and magic-angle spinning (MAS) solid-state 31P NMR. The static 31P NMR spectrum of the three-component membrane is a typical broad powder pattern for phospholipids in a bilayer structure, and is a result of three overlapping spectra of each individual phospholipid component in the mixed membrane, with an average effective chemical shift anisotropy of approximately 41 ppm. Using magic-angle spinning NMR methods, three resolved resonances are observed in the narrowed MAS 31P NMR spectrum, each of which has been assigned to each lipid component in the mixed membrane. This allows the investigation of individual phospholipid-protein interactions in multicomponent lipid bilayers. The interaction of cytochrome c with each lipid in a model mitochondrial membrane could now be evaluated. Phosphorus-31 spin-lattice (T1) relaxation times for each lipid phosphate were measured as a function of temperature, in the absence and presence of bound cytochrome c. T1 was not affected for any lipid upon binding of cytochrome c over the temperature range analyzed. However, averaging of the phosphorus-31 chemical shift anisotropy for the cardiolipin component in mixed PC/PE/CL bilayers at lower temperatures ceases to be axially symmetric on binding of cytochrome c, while for PC and PE components the axial symmetry is retained over the temperature interval studied here.(ABSTRACT TRUNCATED AT 250 WORDS)